Microbial responses and metabolic pathways reveal the recovery mechanism of an anaerobic digestion system subjected to progressive inhibition by ammonia - Chen, Sisi; He, Jin; Wang, Hongyang; Dong, Bin; Li, Ning; Dai, Xiaohu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
•Acidogenesis recovered more quickly than methanogenesis from TAN inhibition.•Methanosarcina dominated the recovered methanogenesis through alternative pathways.•The order Clostridiales mainly contributed to the recovery of biogas production.•Enriched protein-utilizing Tissierella and Lutispora greatly related to recovery.•Protein degradation inhibited during inhibition phases could basically recover. To overcome the bottlenecks for alleviation of ammonia-driven inhibition and realize performance optimization, recovery mechanism of an anaerobic digestion system subjected to progressive inhibition by ammonia were investigated. Methanosarcina whose abundance declined with the increase of ammonium nitrogen concentration, was found to be a quickly recovering archaeal genus, mainly responsible for the recovery of methane production after the severe inhibition. Bacteria belonging to Firmicutes, which played important roles in acidogenesis, were resistant to the elevated total ammonium nitrogen concentration. Importantly, they were also the most rapidly growing population during the recovery. Within the phylum Firmicutes, enriched protein-utilizing genera Tissierella and Lutispora (belong to the order Clostridiales), were found to be greatly correlated with the recovered biogas production and Methanosarcina. Moreover, with the recovery of the biogas production and protein-utilization bacteria, the metabolism of protein which were inhibited during the severe inhibition basically recovered.